Potential Conflict Reduction Through Employee Identity - Hendriyani, Rulita; Prihastuty, Rahmawati; Muhammad, Amri Hana; Azis, Abdul; Gita Pramesti, Bening; Nurfarikhah, Asna; Nareta, Auliya; Agenovindia, Faradita; Permatasari, Bintang (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
Communication is the interpretation of ideas, information and feelings that are useful for employees in managing an organisation and useful for sharing views in order to achieve goals and useful for overcoming conflict. Conflict in organisations if left unchecked can cause negative emotions and lead to interpersonal disputes that can reduce individual and group performance. To reduce conflicts that occur in an organisation, it is necessary to identify employee personalities suchas the MBTI Test or those characters that will show how they behave. Differences in employee personality will also affect how an employee understands interpersonal situations and manages conflict. The research method used is descriptive quantitative. The participants in this study were all employees of CV Laksana Karoseri Ungaran from various divisions and job positions. Not limited by gender, nor the period or length of work, only limited by a minimum age of 20 years. Research participants were taken with purposive sampling technique. The results of this study indicate that the conflict management style that is more widely used by employees of CV Laksana Karoseri Ungaran as much as 53.27% is the Collaborating Style, and only a few employees use the Competing Style in conflict management, as much as 10.05%. This collaborating conflict management style is dominated by estj personalities. In addition to the collaborating conflict management style, this study shows that the second most preferred style after collaborating is compromising. The compromising conflict management style tends to be widely used by CV Laksana Karoseri Ungaran employees with ENFP (Extrovert, Intuition, Feeling, Perceiving) personality type.